2016
DOI: 10.1136/archdischild-2016-311910
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health, growth and gonadal function in children and adolescents with congenital adrenal hyperplasia

Abstract: After the introduction of replacement therapy with glucocorticoids and mineralocorticoids in the 1950s, congenital adrenal hyperplasia (CAH) is no longer a life-limiting condition. However, due to the successful introduction of medical steroid hormone replacement, CAH has become a chronic condition, with associated comorbidities and long-term health implications. The aim of treatment is the replacement of mineralocorticoids and glucocorticoids and the normalisation of elevated androgen concentrations. Long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 93 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…The effects of adrenal sex steroids and glucocorticoids on measures of body composition, such as visceral adipose tissue (VAT) and the Android:Gynoid (A:G) ratio, have not been well studied in children with CAH. This area of investigation is important given that children and adults with CAH may have higher risk for cardiovascular disease compared to the general population . VAT is associated with increased cardiometabolic risk, while the A:G ratio is associated with elevated triglyceride levels and lower HDL levels and is a better predictor of cardiovascular risk than BMI .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of adrenal sex steroids and glucocorticoids on measures of body composition, such as visceral adipose tissue (VAT) and the Android:Gynoid (A:G) ratio, have not been well studied in children with CAH. This area of investigation is important given that children and adults with CAH may have higher risk for cardiovascular disease compared to the general population . VAT is associated with increased cardiometabolic risk, while the A:G ratio is associated with elevated triglyceride levels and lower HDL levels and is a better predictor of cardiovascular risk than BMI .…”
Section: Introductionmentioning
confidence: 99%
“…This area of investigation is important given that children and adults with CAH may have higher risk for cardiovascular disease compared to the general population. 19 VAT is associated with increased cardiometabolic risk, 20 while the A:G ratio is associated with elevated triglyceride levels and lower HDL levels and is a better predictor of cardiovascular risk than BMI. 21 Although the A:G ratio can be calculated from dual-energy X-ray absorptiometry (DXA) measures, 22 data quantitating VAT in children with CAH are limited, and no studies have examined VAT using DXA.…”
mentioning
confidence: 99%
“…Both androgen excess and treatment with supraphysiological doses of glucocorticoids are associated with an unfavourable cardiovascular and metabolic risk profile in patients with CAH . Several studies performed in adult and paediatric patients with CAH showed that they indeed cluster a number of cardiovascular risk factors: obesity, increased fat mass, insulin resistance and high blood pressure .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this finding was also reported in men with classic CAH [ 21 ]. In women, the causes were assigned to factors such as adrenal overproduction of androgens and progestins, neuroendocrine factors, genital surgery and/or psychosocial factors [ 22 ]. However, at this point, one should not confuse the terms fertility and fecundity.…”
Section: Discussionmentioning
confidence: 99%